The Role Model of Prophet Yusuf as a Youth According to Wahbah al-Zuhailî: Keteladanan Nabi Yusuf as sebagai Seorang Pemuda Menurut Wahbah al-Zuhaili (Takwil: Journal of Quran and Hadith Studies, 2022)
The story of Prophet Yusuf as said by Allah as the best story in the Qur'an (Surah Yusuf/12: 3). This story is told in full in one letter without any fragmentation of the story and repetition of the story in other letters. According to Nashruddin Baidan (New Insights on Tafsir Science, Yogyakarta, Pustaka Pelajar: 2005) the stories of the Koran placed by Allah in various letters are scattered and are not mentioned chronologically in a special letter except for the story of the Prophet Yusuf as revealed by Allah. in full in Yusuf's letter. Wahbah al-Zuhailî argues that in Surah Yusuf verse seven Allah mentions that the story of the Prophet Yusuf (as) has an example and 'ibrah. By using qualitative research (Library Research) with the maudhu'i method approach (thematic interpretation) of one letter which focuses on the example of the Prophet Yusuf as a young man, it was found that: first, Prophet Yusuf (as) was classified as 'Ibâdina al-Mukhlashîn, second, Prophet Yusuf as Ista'shama from the wishes of al-Azîz's wife, third, Prophet Yusuf as prefers prison to adultery.